2015
DOI: 10.1039/c5ta02570b
|View full text |Cite
|
Sign up to set email alerts
|

Template-free ultraspray pyrolysis synthesis of N/Fe-doped carbon microspheres for oxygen reduction electrocatalysis

Abstract: Ultrasonic spray pyrolysis was used in a continuous flow apparatus for the template-free synthesis of ironand nitrogen-doped porous carbon materials. Solutions of glucose, histidine and Fe(CH 3 COO) 2 were nebulized and pyrolyzed yielding carbon microspheres. Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS) and Focused Ion Beam (FIB) milling revealed that microspheres initially possess empty cores and a smooth shell. Further annealing leads to a collapse of this shell, and formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 57 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…It was postulated that the iron center coordinated with nitrogen atoms (Fe–N x ) was responsible for the excellent catalytic performance, with electron‐transfer number of 3.86 in KOH electrolyte, close to the value for commercial Pt/C (3.92), as well as better stability (82%) compared to Pt/C (65%) after 35 000 s. In addition, Fe/Fe 3 C@N–graphitic carbon nanocapsules were uniformly formed, preventing stacking of the graphene structure. Morzorati et al developed an ultrasonic spray‐pyrolysis strategy to obtain template‐free Fe,N‐doped carbon spheres in a continuous flow apparatus, using glucose, histidine, and iron acetate …”
Section: Carbohydrates and Polysaccharidesmentioning
confidence: 99%
“…It was postulated that the iron center coordinated with nitrogen atoms (Fe–N x ) was responsible for the excellent catalytic performance, with electron‐transfer number of 3.86 in KOH electrolyte, close to the value for commercial Pt/C (3.92), as well as better stability (82%) compared to Pt/C (65%) after 35 000 s. In addition, Fe/Fe 3 C@N–graphitic carbon nanocapsules were uniformly formed, preventing stacking of the graphene structure. Morzorati et al developed an ultrasonic spray‐pyrolysis strategy to obtain template‐free Fe,N‐doped carbon spheres in a continuous flow apparatus, using glucose, histidine, and iron acetate …”
Section: Carbohydrates and Polysaccharidesmentioning
confidence: 99%
“…Suslick and co‐workers have developed methods for the USP synthesis of porous carbon microspheres (CMs) in the absence of hard templates, which result in carbon materials with high specific surface area. Work from our group has also shown that thus synthesized CMs can be used as support for metal nanoparticles, and that USP methods can be used to prepare metal@CM electrocatalysts . In this work we demonstrate that Pt nanoparticles embedded in porous carbon microspheres (PtCM) can be directly prepared from aqueous precursors in the absence of hard templates using continuous USP; PtCMs were found to display excellent durability and mass activity for the ORR and outstanding tolerance to the methanol‐crossover.…”
Section: Introductionmentioning
confidence: 76%
“…The N content was found to be 3.8%-again a common dopant loading found for NHCSs. Deconvolution of the N peak indicated four types of N atoms [41][42][43]: pyridinic N (21 %; 397,90 eV), pyrollic N (17%; 399.0 eV), graphitic N (45%; 400.82 eV), and N-O (17 %, 402.9 eV). These types of N atoms are found in varying ratios in N-doped graphitic carbon materials, and their ratios were determined by the nitrogen source, the carbon source, and the reaction temperature.…”
Section: Resultsmentioning
confidence: 99%